Selected poems - Brontë, Anne, 1820-1849 (Fyfield books., 2012)
Although the Brontës have long fascinated readers of fiction and biography, their poetry was all too little known until this pioneering selection by Stevie Davies, the novelist and critic. Charlotte (1816-1855) is certainly a competent poet, and Anne (1820-1849) developed a distinctive voice, while Emily (1818-1848) is one of the great women poets in English. Read together with their novels, the poems movingly elucidate the ideas around which the narratives revolve. And they surprise us out of our conventional notions of the sisters' personalities: Emily's rebelliousness, for example, is co.